HUBUNGAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA DENGAN KEMAMPUAN MENULIS RINGKASAN TEKS TAJUK RENCANA - Rosidah Surbakti (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
This study aims to determine the relationship between students' reading comprehension ability and the ability to write editorial text summaries in class VIII Private Dharma Middle School in Medan. The population of this study were all eighth grade students of Dharma Wanita Private Middle School in the 2016/2017 learning year, which amounted to 40 people spread in one class and the study sample was taken as a whole or can be said to be a total population of 40 people. The method used in this research is descriptive correlational method. The instruments used to collect data are multiple choice tests and assignment tests. Based on data processing, the average value of reading comprehension ability of students was 80.875 and included in the excellent category (70%), good (20%) and sufficient (10%). The average value of the ability to write a summary of the editorial text is 72.125 and is included in the excellent category (32.5%), good (42.5%), sufficient (20%). There is a significant relationship between reading comprehension ability and the ability to write an editorial text summary for class VIII students of Medan Women's Dharma Private Middle School.